Survive the night - Vega, Danielle (Razorbill, an imprint of Penguin Random House, 2015)
Fresh out of rehab for oxycodone addiction, Casey and some of her friends attend an all-night rave called Survive the Night in the New York City subway, and find themselves fighting for their lives because drugs are not the only danger here--something is using the rave to attract victims, and some of them will not be coming back.